Heat shock protein genes (hsp20, hsp75 and hsp90) from Pieris rapae: Molecular cloning and transcription in response to parasitization by Pteromalus puparum. (20th June 2012) - Zhu, Jia‐Ying; Wu, Guo‐Xing; Ye, Gong‐Yin; Hu, Cui
<x xml:space="preserve">Abstract</x> Abstract Most molecular work on the roles of heat shock proteins (hsps) in host‐parasite interaction has focused on vertebrates, rather than invertebrates. Here the full length complementary DNA (cDNA) sequences of three hsp genes (hsp20, hsp75 and hsp90) were amplified from Pieris rapae, and their transcriptional responsiveness to parasitization by the endoparasitic wasp Pteromalus puparum were investigated. The cDNA sequence analysis of hsp20, hsp75 and hsp90 revealed open reading frames of 531, 2 328 and 2 157 bp in length, which encode proteins with calculated molecular weights of 19.5, 75.48 and 82.7 kDa, respectively. The comparison of amino acid sequences showed that P. rapae hsp20 shared highly divergent homology to that of other insects, while hsp75 and hsp90 showed high homology to their counterparts of other species. The expression analysis indicated that these three genes were influenced in response to parasitization by P. puparum. The hsp20 transcripts in parasitized pupae were higher compared to non‐parasitized pupae. The expression of hsp75 and hsp90 were down‐regulated following parasitization. The results indicate that hsps are involved in host‐parasitoid interactions.